ASSA13-02-8 Safety, Efficacy and Learning Curve of Catheter Ablation of Paroxysmal Atrial Fibrillation Using Circumferential Pulmonary Vein Isolation Technique in the Single Centre and in a Single Operator. (29th April 2013) - Qiaoli, Ma; Zulu, Wang; Yanchun, Liang; Guitang, Yang; Shibei, Li; Ming, Liang; Zhiqing, Jin; Yaling, Han
Abstract : Background: CARTO anatomical mapping system and circumferential pulmonary vein isolation (CPVI) technique has been used to cure paroxysmal atrial fibrillation (PAF) in most hospitals in China, and have achieved a high success rate. But whether the successful rate, the recurrence rate and the safety are related to learning cure is still unclear. Methods: From December 2004 to December 2010, 258 consecutive patients who underwent CPVI for PAF in our hospital were collected. The patients were divided into three groups with equal patient numbers according to the time sequences. Group I consisted of the first 86 cases, Group II consisted of the second 86 patients, and Group III consisted of the last 86 cases. Age, gender, course of disease, echocardiography, other atrial arrhythmias, basic diseases were analysed statistically. The operation X-ray exposure time, recent recurrence, late recurrence and re-ablation procedures were also analysed. In addition, the learning curve of CPVI for PAF and its relationship with peri-operative period complications, and the risk factors to predict the recurrence of atrial arrhythmias were analysed, too. Results: There were no significant differences in patients' age, gender, basic diseases and LAD among three groups. The rates of early recurrence in Group I, Group II and Group III were 38/86 (44.2%), 26/86 (30.2%) and 21/86 (24.4%) respectively (P < 0.05). The successful rates at 1 year were 44.2%, 51.2%, 64.0% respectively (P < 0.05) in three groups. The incidence of general complications was 12.8% in Group I, 4.7% in Group II, and 2.3% in group III. There were statistically significant differences between the total complication rates among the three groups. In many variables, left atrium dimension (LAD) enlargement and early recurrence were the risk factors of recurrent AF (P < 0.01 and P < 0.05, respectively). Conclusion: For an experienced operator, CPVI has a higher success rate, a lower recurrence and a lower complication rate for radiofrequency catheter ablation of PAF. However, for a beginning operator, the success rate was relatively lower, both the recurrence and the complication rate were higher, and the X-ray exposure time was longer. The strengthened training of CPVI technique for PAF may be very important for the new operator to increase the success and to avoid or decrease the incidence of complications.